Contact transition control with acceleration feedback enhancement for a quadrotor. (March 2021) - Yi, Kui; Han, Jianda; Liang, Xiao; He, Yuqing
Abstract: A stable transition from free-motion to contact phase is extremely significant for a UAV interacting with its objects and environment. Oscillations may occur at the contact point if the force controller of the UAV fails to accommodate to the environment parameters, which are usually unknown to the UAV. In this paper, the acceleration feedback control is proposed to enhance the robustness of a classic force controller. This intends to achieve a smooth and stable contact transition of the UAV while interacting with different stiffness environments with non-zero approaching velocity. Extensive flight tests are conducted on a quadrotor UAV to verify the performance of the proposed algorithm with respect to different-stiffness environments. The experimental results are also compared with those without the acceleration feedback enhancement, to demonstrate the improvement of the proposed scheme. Highlights: An acceleration feedback control is proposed as an enhancement. The acceleration feedback control serves as extra damping. Experimental results demonstrate the improvements obtained by the proposed scheme.